A clinical study of microwave ablation for cervical lymph node metastasis from papillary thyroid cancer - Wu, Jie; Wei, Ying; Zhao, Zhen-long; Cao, Shi-liang; Li, Yan; Peng, Li-li; Li, Shu-qi; Yu, Ming-an (Frontiers in Endocrinology, 2025)
PurposeThe aim of this study is to evaluate the efficacy and safety of microwave ablation (MWA) for cervical lymph node metastasis (LNM) in initially treated, post-ablation and post-resection papillary thyroid cancer (PTC) patients.MethodsA total of 131 patients with 535 LNM from PTC who underwent ultrasound-guided MWA were included in the retrospective study. Patients were divided into three subgroups on the basis of treatment timing: initially treated, after PTC ablation (post-ablation), or after resection (post-resection). Changes in cervical metastatic lymph nodes as well as the incidences of complications, tumour recurrence and progression were compared.ResultsThe technical success rate of this study was 100% (535/535). Compared with those before MWA, the mean largest diameter and volume of the metastatic lymph nodes were significantly lower (p <0.01) at each follow-up. Transient hoarseness was the exclusive major complication with a total rate of 5.3% (9/171), which significantly differed in terms of incidence among the three subgroups (p<0.01). Lymph node location in region VI was an independent risk factor for transient hoarseness. The total recurrence rate was 22.8% (39/171) without statistically significant difference among the three sub-groups (p=0.20). Two cases received repeated surgery, while re-ablation was conducted successfully in all rest of cases. Data from the latest follow-up revealed one death due to LNM.ConclusionMWA is a safe and effective treatment option for LNM in initially treated, post-resection and post-ablation PTC patients.